Ադրբեջան-Արցախ հարյուրամյա հակամարտության փոխակերպումները իրադարձային հենքի և իրավաքաղաքական արդյունքների դիտակետից - Մանասյան, Ալեքսանդր (YSU Journal of International Affairs, 2018)
The article considers the legal and political transformation of the Nagorno-Karabakh-Azerbaijan 100-year conflict in the pre-Soviet, Soviet and post-Soviet periods of its history. The centennial experience of Azerbaijan-Nagorno-Karabakh conflict is strictly inaccurate for both policy-makers and mediators, both for law and policy theorists. They are viewed from the point of view of the main events and outcomes of the discussed circles. It is shown how Nagorno-Karabakh has reached a state of de facto international status from the disputed territory of 1918-1920 as a party to the conflict and negotiation process, protecting its sovereignty in the battlefield due to armed confrontation and political struggle. The author touches upon the issues of the conflict of legal and political factors in the international arena, the overcoming of which can play a decisive role in the recovery of the international life.
Keywords: Karabakh Conflict, Stages of Karabakh Conflict, Politicalization of Conflict under the Rule of Law, Ethno-Political Conflict, Caucasian Tatar, Stalin project to build Azerbaijani nationality